2019
DOI: 10.1039/c9nj01551e
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient structurally characterised novel precatalysts: di- and mononuclear heteroleptic Cu(i) dixanthate/xanthate–phosphine complexes for azide–alkyne cycloadditions

Abstract: Prominent catalytic activities of novel di- and mononuclear Cu(i) xanthate/phosphine complexes have been investigated for the synthesis of triazolyl glycoconjugates using Click approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Singh and co-workers, in the same year, synthesized five dinuclear/mononuclear heteroleptic copper­(I) dithio complexes, well elucidated by single crystal XRD . The efficiency of the resulting catalysts was optimized on the basis of reaction time, holding all other reaction conditions constant, for the model reaction of click counter parts glycosyl azide ( 39 ) and alkyne (phenylacetylene) scaffold.…”
Section: Generalities About Cuaac Click Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Singh and co-workers, in the same year, synthesized five dinuclear/mononuclear heteroleptic copper­(I) dithio complexes, well elucidated by single crystal XRD . The efficiency of the resulting catalysts was optimized on the basis of reaction time, holding all other reaction conditions constant, for the model reaction of click counter parts glycosyl azide ( 39 ) and alkyne (phenylacetylene) scaffold.…”
Section: Generalities About Cuaac Click Chemistrymentioning
confidence: 99%
“…Furthermore, this catalyst was implemented for the development of a library of triazolyl glycoconjugates ( 43 ) via modular CuAAC reaction of azide with alkyne at room temperature (Scheme ). The catalyst efficiency and reusability was proven by an NMR study that showed triazolyl glycoconjugate formation in 2 h with good-to-excellent yields and seven times of reuse without any notable loss of its catalytic activity.…”
Section: Generalities About Cuaac Click Chemistrymentioning
confidence: 99%
“…19 N donor ligands, such as tris(2-dioctadecylaminoethyl)amine, tristriazolylamines, tris(benzimidazolylmethyl)amines, 20,21 and ligands with C donating capacity, particularly NHC ligands 22 have exhibited outstanding activity towards CuAAC, whereas O/S donor ligands remain merely investigated. 13,[23][24][25][26] With the turn of the 21st century, there has been an increasing interest in the synthesis of ''pre-formed'' copper(I) complexes acting as catalysts in CuAAC reactions. [23][24][25][26] Recently, a number of Cu(I) complexes were synthesized in our laboratory, which showed excellent compatibility with CuAAC reaction conditions to generate triazolylglycoconjugates in high yields.…”
Section: Introductionmentioning
confidence: 99%
“…13,[23][24][25][26] With the turn of the 21st century, there has been an increasing interest in the synthesis of ''pre-formed'' copper(I) complexes acting as catalysts in CuAAC reactions. [23][24][25][26] Recently, a number of Cu(I) complexes were synthesized in our laboratory, which showed excellent compatibility with CuAAC reaction conditions to generate triazolylglycoconjugates in high yields. Among the various classes of glyco-architectures that can be designed through CuAAC, glycoclusters have gained exceeding popularity owing to their use in drug discovery, therapeutics and photophysical studies.…”
Section: Introductionmentioning
confidence: 99%
“…us, there is an increased demand of suitable click catalysts for efficient CuAAC coupling. Towards this end, a number of promising such catalysts such as mono-and dinuclear heteroleptic Cu(I) dithio-PPh3 complexes [32], di-and mononuclear heteroleptic Cu(I) dixanthate/xanthate-phosphine complexes [33], heteroleptic [Cu(PPh 3 ) 2 (β-oxodithioester)] complexes [34], thiocarboxylate complexes, and cubane-based hydrosulfide complexes of Cu(I) [35] were displayed efficient catalytic activities for the click conjugation with carbohydrates. Among all, a highly stable Cu(I) catalyst [(PPh 3 ) 2 Cu(μ-tda) Cu(PPh 3 ) 2 ].6H 2 O with significant catalytic activity has been copiously exploited for the thriving construction of regioselective 1,4-disubstituted dendritic architectures [36].…”
Section: Introductionmentioning
confidence: 99%